2012
DOI: 10.1158/0008-5472.can-12-1317
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Ectopic Grafting of Cryopreserved Testicular Tissue Preserves the Fertility of Prepubescent Monkeys That Receive Sterilizing Cytotoxic Therapy

Abstract: Boys faced with future sterility as a result of the need of a sterilizing cancer therapy might avoid this fate by engraftment of cryopreserved immature testicular tissue after therapy is completed. Efforts to address this important survivorship issue have been encouraged by reports of the long-term survival and proliferation of human spermatogonia after xenotransplant of cryopreserved immature testicular tissue into immunocompromised murine hosts. However, spermatogenic arrest at the pachytene spermatocyte sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 21 publications
0
67
0
Order By: Relevance
“…Testis autografting has been shown to be a feasible option for production of sperm in monkeys (Jahnukainen et al 2012). However, autologous immature testis grafts in the marmoset matured to meiosis, but normal serum testosterone level was not restored (Wistuba et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Testis autografting has been shown to be a feasible option for production of sperm in monkeys (Jahnukainen et al 2012). However, autologous immature testis grafts in the marmoset matured to meiosis, but normal serum testosterone level was not restored (Wistuba et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since earlier studies have shown no difference in survival and development of xenografts in both castrated and intact (noncastrated) mouse recipients [25,26], cryopreserved testicular tissues were xenografted onto intact nude mice. Cryopreserved rhesus monkey testes could establish spermatogenesis in intact mice [27] but not in castrated mice [28], indicating that intact mice support spermatogenesis in cryopreserved testes. Seminal vesicle weight of recipients that were grafted with testis tissues that had been cryopreserved in either cryomedia was not different from the age-matched control, indicating normal serum testosterone levels.…”
Section: Discussionmentioning
confidence: 95%
“…Presently, there are no reported human live births originating from sperm obtained from cryopreserved testes [33]. Although sperm can be obtained by grafting thawed testes [34] or transplanting spermatogonial stem cells into testes [35,36] in nonhuman primates, there is a risk of reintroducing malignant cells. These procedures are also quite invasive to patients.…”
Section: Necessity For Establishing Oncofertility Network Worldwidementioning
confidence: 99%